DNA barcoding reveals different cestode helminth species in northern European marine and freshwater ringed seals - Nyman, Tommi; Papadopoulou, Elena; Ylinen, Eeva; Wutke, Saskia; Michell, Craig T.; Sromek, Ludmila; Sinisalo, Tuula; Andrievskaya, Elena; Alexeev, Vyacheslav; Kunnasranta, Mervi
2021